Effect of a cross-flow perforated tube on pressure pulsation and pressure loss in a reciprocating compressor piping system. (February 2017) - Liu, Zhan; Cheng, Junming; Feng, Quanke; Yu, Xiaoling
This paper experimentally investigates the effects of a cross-flow perforated tube on the pressure pulsation attenuation and pressure loss in a reciprocating compressor piping network, with particular focus on the structure parameters and installation positions. The results demonstrate that significant pressure fluctuation attenuation and less pressure loss in the whole piping system can be achieved when a well-designed cross-flow perforated tube is installed downstream of the pulsating bottle. The pressure pulsation is reduced as the perforated rate decreases and as the perforated tube length increases, while the hole diameter has little effect upon the pulsation attenuation. In the aspect of reducing pressure loss, the perforated rate should be larger than 0.05 and the hole diameter should be larger than 8 mm. In addition, a pressure pulsation computation model based on the linear acoustic wave theory and transfer matrix method is developed to predict the pulsating pressure in compressor piping systems with an installed cross-flow perforated tube. With favorable agreement between the model prediction and the present experimental results (maximum deviation within 6.8%), the predicted pulsating pressure can be attenuated for the reciprocating compressor piping system with various compressor speeds when a cross-flow perforated tube is reasonably designed and installed.